Isolation and identification of bacteria and parasites in glass eel (Anguilla spp.) - Andriyanto Septyan (EDP Sciences, 2021)
The disease is the main agent that causes mortality of fish, especially during seed stages. The research aimed to find out bacteria and parasitic speciesin glass eel, Anguilla spp. Bacterial identification was carried out by a biochemical method. The prevalence of bacterial species was calculated using the El-Gohary et al. (2020) formula, while the results of bacterial identification from glass eel were Aeromonas spp., Vibrio spp., Enterococcus spp., Staphylococcus spp., Planococcus spp., Lactobacillus spp., Listeria spp., Citrbacterfreundii, Neisseria spp., Pseudomonas aeruginosa, Kurthia spp., Streptococcus spp., and Corynebacterium spp. It was found that the five highest prevalence rate was for Listeria spp. (39.64%), followed by Aeromonas spp. (26.13%), Staphylococcus spp. (16.22%), Corynebacterium spp. (5.41%), Lactobacillus spp. (2.70%), and the lowest prevalence rate was Streptococcus spp. (0.90%). The type of parasitic pathogen obtained was Trichodina spp. (2,70%), Dactylogyrus spp. (2,70%) and Gyrodactylus spp. (2,70%). Bacterial and parasites identified in glass eels need further verification on the epizootiology characteristic of each pathogenic agent.